2023
DOI: 10.1111/bju.15978
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the TRANSLATE prospective, multicentre, randomised clinical trial of prostate biopsy technique

Abstract: Objectives Primary objectives: to determine whether local anaesthetic transperineal prostate (LATP) biopsy improves the detection of clinically significant prostate cancer (csPCa), defined as International Society of Urological Pathology (ISUP) Grade Group ≥2 disease (i.e., any Gleason pattern 4 disease), compared to transrectal ultrasound‐guided (TRUS) prostate biopsy, in biopsy‐naïve men undergoing biopsy based on suspicion of csPCa. Secondary objectives: to compare (i) infection rates, (ii) health‐related q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Two ongoing European multicenter randomized controlled trialsdPERFECT and TRANSLATEdare designed to compare clinically significant prostate cancer detection rates between TP and TR biopsy. 4,5 Despite a lack of robust evidence for superiority, some have advocated that TP biopsy should completely replace TR biopsy. Given the similar safety profiles based on this trial, perhaps TR biopsy should not be discarded altogether but used selectively in cases where it may be helpful.…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Two ongoing European multicenter randomized controlled trialsdPERFECT and TRANSLATEdare designed to compare clinically significant prostate cancer detection rates between TP and TR biopsy. 4,5 Despite a lack of robust evidence for superiority, some have advocated that TP biopsy should completely replace TR biopsy. Given the similar safety profiles based on this trial, perhaps TR biopsy should not be discarded altogether but used selectively in cases where it may be helpful.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Two ongoing European multicenter randomized controlled trials—PERFECT and TRANSLATE—are designed to compare clinically significant prostate cancer detection rates between TP and TR biopsy. 4,5…”
mentioning
confidence: 99%
“…Details of the Health Economics analyses are described in the study protocol (2) and will be undertaken separately by a Health Economist.…”
Section: Supplementary Analyses and Outcomesmentioning
confidence: 99%
“…On the other hand, some early studies concluded that TP biopsy under LA may be significantly more painful than a TR biopsy under LA ( 16 - 18 ). More recent studies have shown comparable pain scores ( 19 - 21 ) and a large multicenter, randomized trial aimed to provide high-quality evidence has been developed ( 22 ). Also, given that some patients may still require conversion to sedation during TP under LA ( 12 ), the knowledge gap in regard to which patients would be more likely to experience higher degree of pain during the procedure, appears to be clinically significant.…”
Section: Introductionmentioning
confidence: 99%